Agreement between the EU and Turkey on the readmission of persons residing without authorisation - Ün, Ayşegül (My University, 2019)
Bu tez, Avrupa Birliği Geri Kabul Antlaşmalarının uygulama alanı ve temelhukuki dayanaklarını değerlendirme amacıyla yazılmıştır. Öncelikle, bu tezde düzensizgöçle mücadele etmek için hedef alınan üçüncü ülkelerle yapılan Avrupa Birliği GeriKabul Antlaşmalarının ana hatlarını belirleyen unsurlar incelenmiştir. İkinci olarak,Avrupa Birliği ve üye devletlerinin Geri Kabul Antlaşmaları kapsamında yetki alanlarıve türleri, bu yetkilerden doğan sorumluluklarıyla beraber analiz edilmiştir. Üçüncüolarak, Türkiye Cumhuriyeti ile Avrupa Birliği arasında izinsiz ikamet eden kişileringeri kabulüne ilişkin Antlaşmanın koşulları ve akit taraflara belirlediği yükümlülüklerele alınmıştır. Takiben, bu antlaşmanın uygulanmasını ve yürürlüğe konmasını etkileyenve engelleyen sorunlar, ilgili iltica ve insan hakları hukukunu da içererek tespitedilmiştir.

This thesis seeks to determine the European Union Readmission Agreements within its scope of application andits legal basis. The first aim on the thesis focuses on the outlines of the Readmission Agreements concluded by theEuropean Union targeting third countries to combat with irregular migration. Secondly, the division of the use of powers and along with their responsibilities arisen by the European Union and its Member States are analysed. Thirdly, the Agreement between the European Union and the Republic of Turkey on the readmission of persons residing without authorisation is scrutinized in relation with its clauses and provisions. And followingly, the deficiencies on the implementation and application of the Readmission Agreement are reviewed in conjunction with human rights and asylum law.
Keywords: Avrupa Birliği; Avrupa Birliği Geri Kabul Antlaşmaları; EU-TurkeyReadmission Agreement; European Union; Hukuk; Law; Türkiye AB Geri Kabul Antlaşması European Union Readmission Agreements